2012
DOI: 10.1371/journal.pone.0031712
|View full text |Cite
|
Sign up to set email alerts
|

Human Alpha Defensin 5 Expression in the Human Kidney and Urinary Tract

Abstract: BackgroundThe mechanisms that maintain sterility in the urinary tract are incompletely understood. Recent studies have implicated the importance of antimicrobial peptides (AMP) in protecting the urinary tract from infection. Here, we characterize the expression and relevance of the AMP human alpha-defensin 5 (HD5) in the human kidney and urinary tract in normal and infected subjects.Methodology/Principal FindingsUsing RNA isolated from human kidney, ureter, and bladder tissue, we performed quantitative real-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
66
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 38 publications
4
66
0
6
Order By: Relevance
“…Moreover, LRRC19 expressed in kidney tubular cells not only modulated the expression of inflammatory cytokines but also antimicrobial peptides and proteins, such as a-defensin-5, Reg3g and cathelicidin. Importantly, we found that LRRC19-deficient kidney tubular cells also have a reduced ability to kill UPEC, consistent with the fact that the antimicrobial substances have antibacterial activity against common uropathogenic Grampositive bacteria and Gram-negative bacteria 6,[8][9][10] . Thus, LRRC19 in kidney tubule cells is involved not only in attracting inflammatory cells but also in kidney-mediated killing of uropathogenic bacteria.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Moreover, LRRC19 expressed in kidney tubular cells not only modulated the expression of inflammatory cytokines but also antimicrobial peptides and proteins, such as a-defensin-5, Reg3g and cathelicidin. Importantly, we found that LRRC19-deficient kidney tubular cells also have a reduced ability to kill UPEC, consistent with the fact that the antimicrobial substances have antibacterial activity against common uropathogenic Grampositive bacteria and Gram-negative bacteria 6,[8][9][10] . Thus, LRRC19 in kidney tubule cells is involved not only in attracting inflammatory cells but also in kidney-mediated killing of uropathogenic bacteria.…”
Section: Discussionsupporting
confidence: 82%
“…Consistent with other data [6][7][8][9] , kidney also expressed different kinds of bactericidal substance ( Supplementary Fig. 6a).…”
Section: Lrrc19 Promotes Expression Of Antimicrobial Substancessupporting
confidence: 92%
See 1 more Smart Citation
“…HD5 showed bactericidal activity at minimal concentration of 0.3 M [58]. However, it is reported that HD5 does not reach sufficient concentrations to kill bacteria in the urinary tract [59]. The role of HD5 in innate immunity of urinary tract is not fully known.…”
Section: ) -Defensins -Defensins Are Human Neutrophil Peptides (Hnmentioning
confidence: 99%
“…Renal ribonuclease 7 expression is limited to ICs, constitutively expressed at baseline, upregulated in response to infection, and secreted into the urine (42,43). ICs have been demonstrated to express other innate immune proteins, including neutrophil gelatinase-associated lipocalin, also known as lipocalin 2 (gene: Lcn2; protein: Ngal), IL-18 (gene: Il18), and human ␣-defensin 5 (15,28,41). Additionally, uropathogenic Escherichia coli (UPEC) preferentially adhere to the luminal surface of medullary ICs (10).…”
mentioning
confidence: 99%